Magnetocontrollability of Fe7C3@C superparamagnetic nanoparticles in living cells. Issue 1 (December 2016) - Alieva, Irina; Kireev, Igor; Garanina, Anastasia; Alyabyeva, Natalia; Ruyter, Antoine; Strelkova, Olga; Zhironkina, Oxana; Cherepaninets, Varvara; Majouga, Alexander; Davydov, Valery; Khabashesku, Valery; Agafonov, Viatcheslav; et al.
Abstract Background A new type of superparamagnetic nanoparticles with chemical formula Fe7C3@C (MNPs) showed higher value of magnetization compared to traditionally used iron oxide-based nanoparticles as was shown in our previous studies. The in vitro biocompatibility tests demonstrated that the MNPs display high efficiency of cellular uptake and do not affect cyto-physiological parameters of cultured cells. These MNPs display effective magnetocontrollability in homogeneous liquids but their behavior in cytoplasm of living cells under the effect of magnetic field was not carefully analyzed yet. Results In this work we investigated the magnetocontrollability of MNPs interacting with living cells in permanent magnetic field. It has been shown that cells were capable of capturing MNPs by upper part of the cell membrane, and from the surface of the cultivation substrate during motion process. Immunofluorescence studies using intracellular endosomal membrane marker showed that MNP agglomerates can be either located in endosomes or lying free in the cytoplasm. When attached cells were exposed to a magnetic field up to 0.15 T, the MNPs acquired magnetic moment and the displacement of incorporated MNP agglomerates in the direction of the magnet was observed. Weakly attached or non-attached cells, such as cells in mitosis or after cytoskeleton damaging treatments moved towards the magnet. During long time cultivation of cells with MNPs in a magnetic field gradual clearing of cells from MNPs was observed. It was the result of removing MNPs from the surface of the cell agglomerates discarded in the process of exocytosis. Conclusions Our data allow us to conclude for the first time that the magnetic properties of the MNPs are sufficient for successful manipulation with MNP agglomerates both at the intracellular level, and within the whole cell. The structure of the outer shells of the MNPs allows firmly associate different types of biological molecules with them. This creates prospects for the use of such complexes for targeted delivery and selective removal of selected biological molecules from living cells.